Discrimination and Acculturation Stress: A Longitudinal Study of Children's Well-Being from Prenatal Development to 5 Years of Age. Issue 7 (September 2016) - Zeiders, Katharine H.; Umaña-Taylor, Adriana J.; Jahromi, Laudan B.; Updegraff, Kimberly A.; White, Rebecca M. B.
ABSTRACT: Objective: To examine whether cumulative family discrimination and acculturation stress (prenatally to 24 months postpartum) among Mexican-origin adolescent mothers and their mother-figures predicted children's socio-emotional functioning and academic achievement at 5 years of age, and the role of maternal depressive symptoms and mother–child interactions in the association. Method: Mexican-origin families (N = 204) with an adolescent mother, a child, and a mother-figure participated in a 6-wave longitudinal study (2007–2013). Families were recruited and interviewed during the adolescent mother's pregnancy; adolescent mothers, mother-figures, and children were then assessed annually for the next 5 years using a combination of interview-based survey and observational methods. Maternal reports of children's socio-emotional behaviors (measured using the Child Behavior Checklist) and children's academic achievement (assessed with the Woodcock Johnson III Tests of Achievement/Bateria III Woodcock-Muñoz) were used. Results: Structural equation modeling revealed that greater cumulative family discrimination and acculturation stress from pregnancy to 24 months postpartum predicted higher adolescent mothers' depressive symptoms, greater mother–child intrusive interactions, and less mother sensitivity at 36 months postpartum. Maternal depressive symptoms were positively related to children's CBCL symptoms at 60 months postpartum. Greater cumulative discrimination and acculturation stressors directly predicted children's lower Woodcock Johnson/Bateria test scores after accounting for socio-economic status. Conclusion: Mexican-origin adolescent mothers' and mother figures' cumulative discrimination and acculturation stress from pregnancy through children's second birthday predicted children's socio-emotional and academic achievement at age 5. Overall, the findings underscore the cumulative impact of these stressors on well-being in a population with substantial public health significance.